A rare case of amyloidoma of parotid gland - Maingi, Sahil; Sharma, Nishi; Gupta, Ankur; Sofia, Ancy S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Amyloidoma is a solitary, localized tumor like deposit of amyloid. Amyloidosis can be hereditary or acquired, and it may either be systemic or localized. Amyloidoma of the parotid is a very rare condition, and only a few cases have been described in the literature so far. We report a case of 62 years old male presented with right parotid swelling from last 7 months. Till date only 1 case have been reported so far in the literature. This case has been reported due to rarity of its presentation.